PENGARUH LAMA PEMANASAN TERHADAP SIFAT FISIKOKIMIA DAN AKTIVITAS ANTIOKSIDAN EKSTRAK VCO DARI CAMPURAN KUNYIT, JAHE GAJAH, BAWANG PUTIH DAN DAUN SIRIH (THE INFLUENCE OF HEATING DURATION ON THE PHYSICOCHEMICAL PROPERTIES AND ANTIOXIDANT ACTIVITY OF VCO EXTRACT FROM A MIXTURE OF TURMERIC, GINGER, GARLIC, AND BETEL LEAF) - Wibowo, Muhamad Agus; Pitri, Sela Rahma; Ardiningsih, Puji; Jayuska, Afghani (Indonesian Journal of Pure and Applied Chemistry, 2024)
The addition of spices to herbal oil increases bioactivity and physicochemical properties. Turmeric, ginger, garlic, and betel leaf are herbal plants that have the potential to enhance the antioxidant activity and physicochemical properties of herbal oil. This study aims to evaluate the effect of heating temperature on the phytochemical content, physicochemical properties, and antioxidant activity of VCO-based herbal oil with the addition of these spices. The research methods include phytochemical analysis, physicochemical analysis, and antioxidant activity testing using the DPPH method. The herbal oil was prepared at 100 °C with a ratio of herbal plants to VCO of 4:30, and heating durations of 15, 30, 60, and 120 minutes were varied. The results show the presence of flavonoids, terpenoids, saponins, phenolics, and alkaloids in the herbal oil, while VCO contains flavonoids, terpenoids, saponins, and alkaloids, with the addition of herbal plants providing additional phenolic compounds. Physicochemical testing of the herbal oil formulations with heating durations of 15; 30; 60; and 120 minutes respectively shows water content of 0.0923; 0.0189; 0.0165; and 0.0123%, density of 0.98522; 1.02854; 1.55110; and 1.1227 g/mL, acidity level of 4.12; 4.80; 4.28; and 4.38, free fatty acid content of 0.0018; 0.0021; 0.00162, and 0.0029%, and peroxide value of 0.0021; 0.0035; 0.0035; and 0.0042 meq/kg. The IC50 value obtained from the antioxidant activity testing of the herbal oil formulation with a heating duration of 60 minutes is 577.3 ppm, while for VCO, the IC50 obtained is 1029.6 ppm. This indicates that the addition of spices and herbal plants can enhance the bioactivity of VCO-based herbal oil formulations. The addition of spices and herbal plants increases phytochemical content and antioxidant activity, but longer heating durations may decrease the physicochemical properties of herbal oil formulations